2020
DOI: 10.3390/biomedicines8010015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antifungal Activities of Ethnobotanical Ficus hirta Vahl. and Analysis of Main Constituents by HPLC-MS

Abstract: The medicinal and edible plant, Ficus hirta Vahl. (also called hairy fig), is used for the treatment of constipation, inflammation, postpartum hypogalactia, tumors, and cancer. There is an urgent need for scientific evaluation to verify the pharmacological properties of F. hirta. Therefore, in vitro assays evaluated the antioxidant and antifungal activities of various solvent extracts of hairy fig fruits (HFF). HFF extracts had abundant antioxidant components for a significant amount of total phenolic (TPC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
(97 reference statements)
2
7
0
Order By: Relevance
“…There is a general consensus that the antifungal effect of plants might be associated with their content of secondary metabolites. Our results are in line with previous findings as plant antifungal activity was moderately to strongly correlated with phenolic and flavonoid contents (R 2 ≥ 0.527) [30,31]. In fact, E. torquata and C. atlantica that showed the greatest concentrations of polyphenols and flavonoids induced the strongest inhibition effects.…”
Section: Discussionsupporting
confidence: 93%
“…There is a general consensus that the antifungal effect of plants might be associated with their content of secondary metabolites. Our results are in line with previous findings as plant antifungal activity was moderately to strongly correlated with phenolic and flavonoid contents (R 2 ≥ 0.527) [30,31]. In fact, E. torquata and C. atlantica that showed the greatest concentrations of polyphenols and flavonoids induced the strongest inhibition effects.…”
Section: Discussionsupporting
confidence: 93%
“…Among plant extracts, Ficus hirta Vahl. fruit is a common medicine and food that is widely distributed in southern China, and has gained a great deal of attention as an alternative antifungal agent due to its antifungal and antioxidant capacity owing to its high flavonoid content [18,23,31]. In our previous study, we confirmed that P7G isolated from F. hirta Vahl.…”
Section: Discussionsupporting
confidence: 61%
“…The effects of P7G on lesion diameter and disease severity in navel oranges were determined following the method previously described with slight modifications [30,31]. The sterilized navel oranges were wounded (4 mm diameter and 2-mm deep) using a sterile puncher at the equatorial side on each fruit, and then divided in five randomized groups for various P7G treatment levels (0, 1, 2, 4, and 8 g/L).…”
Section: In Vivo Antifungal Activity Assay On Navel Orange Fruitmentioning
confidence: 99%
“…Besides, we found the highest yield with water (≈236 mg) and the lowest (≈10 mg) with butanol. Our results in terms of yield and cytotoxic activity are justified as different nature of solvents extracted different amount and types of metabolites found in a plant, e.g., water extract usually is enriched in large polysaccharides, proteins, etc., and thus, it gives the highest yield [ 26 ], and other solvents extracted various amounts of berberine and other cytotoxic alkaloids/phenolic compounds which is why they exhibited different activity ranges and IC 50 values [ 12 ]. Current findings are supported by the highest amount of berberine and phenolic compounds in a BLE extract as indicated in Table 2 as well as approved by previous studies on other types of cancer cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%